2012
DOI: 10.1108/13527591211241006
|View full text |Cite
|
Sign up to set email alerts
|

Empowering the project team: impact of leadership style and team context

Abstract: PurposeThis paper aims to examine the impact of leadership style and team context on structural and psychological empowerment perceptions in project teams.Design/methodology/approachIt was posited that span of control and within team interdependence will positively and significantly influence both structural and psychological empowerment. Person‐orientated leadership style was also expected to positively impact both structural and psychological empowerment while task orientated leadership style was expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 92 publications
(136 reference statements)
0
1
0
4
Order By: Relevance
“…These variables are closely related to empowerment practices; thus, it is elucidated that empowerment might lead to improved organisational performance. Morgan Tuuli et al (2012) found varying degrees of the positive relationship of task-orientated leadership and person-orientated leadership with three types of project teams, i.e., contractor teams, consultant teams, and client teams. Employees who feel themselves psychologically empowered experience a sense of ownership regarding their organisation and regarding their job responsibilities.…”
Section: The Moderating Role Of Employee Creativitymentioning
confidence: 99%
“…These variables are closely related to empowerment practices; thus, it is elucidated that empowerment might lead to improved organisational performance. Morgan Tuuli et al (2012) found varying degrees of the positive relationship of task-orientated leadership and person-orientated leadership with three types of project teams, i.e., contractor teams, consultant teams, and client teams. Employees who feel themselves psychologically empowered experience a sense of ownership regarding their organisation and regarding their job responsibilities.…”
Section: The Moderating Role Of Employee Creativitymentioning
confidence: 99%
“…Dari pemerhatian kajian lepas, kepimpinan telah didapati secara positif dapat dikaitkan dengan prestasi pekerja (Liden et al, 2008;Zaccaro, Rittman, & Marks, 2001). Ketua pasukan atau penyelia yang memperkasakan kepemimpinan mempunyai hubungan yang positif dengan pembangunan kepimpinan bersama, seterusnya memberi impak positif kepada prestasi (Fausing, Joensson, Lewandowski, & Bligh, 2015;Tuuli, Rowlinson, Fellows, & Liu, 2012;Lee, Lee, & Park, 2014). Pengurus atau pemimpin dapat meningkatkan prestasi organisasi melalui amalan tingkah laku seseorang pemimpin, secara tidak langsung dapat melahirkan kepercayaan pengikut dalam kepercayaan dengan maklumat yang disampaikan oleh ketua (Joseph & Winston, 2005;Errol & Bruce, 2005).…”
Section: Hipotesis 2: Kepimpinan Memperkasa Gelagat Mempunyai Hubunga...unclassified
“…Ini disokong dengan kajian Liden et al, (2008) dan Zaccaro et al, (2001) bahawa kepimpinan telah didapati secara positif dapat dikaitkan dengan prestasi pekerja. Ketua pasukan atau penyelia yang memperkasakan kepemimpinan mempunyai hubungan yang positif dengan pembangunan kepimpinan bersama, seterusnya memberi impak positif kepada prestasi (Fausing et al, 2015;Tuuli et al, 2012;Lee et al, 2014). Malah Skill development (pembangunan kemahiran) dan coaching (kejurulatihan) untuk prestasi yang inovatif, di mana pemimpin mewujudkan peluang untuk latihan dan meningkatkan kemahiran orang bawahan (Konczak et al, 2000;Pearce & Sims, 2002).…”
Section: Perbincanganunclassified
See 1 more Smart Citation
“…Estudos recentes sobre a temática apontam que a liderança exerce efeito sobre o desempenho da organização, quer seja efeito direto (Cherian & Farouq, 2013); quer seja moderado por outras variáveis (Wu, 2014). Além disso, os estilos de liderança também estão relacionados ao comprometimento dos empregados (Garg & Ramjee, 2013;Zanini, Santos, & Lima, 2015); à satisfação no trabalho (Chavaglia, Dela Coleta, Dela Coleta, Mendes, & Trevizan, 2013;Judge & Kammeyer-Mueller, 2012), ao empowerment, contexto e desempenho de equipes de trabalho (Dias & Borges, 2015;Tuuli, Rowlinson, Fellows, & Liu, 2012); bem como à aprendizagem organizacional, sobretudo em termos de capacidade de absorção (Sun & Anderson, 2012); e aprendizagem no trabalho, voltada para as estratégias de aprendizagem (Lins & Borges-Andrade, 2014) ou para os resultados de treinamento (Silva & Mourão, 2015).…”
unclassified